2019
DOI: 10.1001/jamaoto.2018.3793
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Red Blood Cell Distribution Width and Outcomes of Open Airway Reconstruction Surgery in Adults

Abstract: aryngotracheal stenosis (LTS) is a life-threatening, fixed, extrathoracic restriction in pulmonary ventilation. It is an umbrella term that encompasses airway compromise at the level of the larynx, subglottis, or cervical trachea and is a common consequence of multiple pathophysiologic processes. 1-3 The goal of surgical treatment is to improve airway caliber to mitigate the patient's dyspnea and achieve prosthesisfree breathing (eg, without tracheostomy, intraluminal stent, or T-tube). 2,4-10 Successful surgi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 41 publications
(99 reference statements)
0
12
0
Order By: Relevance
“…It is reported that RDW correlated with IL‐6, tumor necrosis factor‐alpha, and other circulating cytokines that can affect the tumor cell biological behavior . Patients with the higher RDW are more likely to have a poorer prognosis than those with the lower RDW, an increased RDW can increase reactive oxygen species and induce tissue hypoxia, associated with an increased risk of postoperative complications . Additionally, a high RDW due to inflammatory cytokines results in increased hepcidin levels, which then reduce RBC production, causing anemia .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is reported that RDW correlated with IL‐6, tumor necrosis factor‐alpha, and other circulating cytokines that can affect the tumor cell biological behavior . Patients with the higher RDW are more likely to have a poorer prognosis than those with the lower RDW, an increased RDW can increase reactive oxygen species and induce tissue hypoxia, associated with an increased risk of postoperative complications . Additionally, a high RDW due to inflammatory cytokines results in increased hepcidin levels, which then reduce RBC production, causing anemia .…”
Section: Discussionmentioning
confidence: 99%
“…7 Patients with the higher RDW are more likely to have a poorer prognosis than those with the lower RDW, an increased RDW can increase reactive oxygen species and induce tissue hypoxia, associated with an increased risk of postoperative complications. 42 Additionally, a high RDW due to inflammatory cytokines results in increased hepcidin levels, which then reduce RBC production, causing anemia. 43 Higher RDW in patients with glioma may be attributed to a variety of underlying metabolic abnormalities, such as inflammation, oxidative stress, and poor nutritional status.…”
Section: Complex Interactions Between Tumor Cells and Inflammatory Cymentioning
confidence: 99%
“…However, different patient and stenosis characteristics have been suggested in the literature as predictors of success in airway surgery. [4][5][6][7]22,37 Therefore, future prospective studies should compare them to establish the most reliable forecaster of decannulation, onset of complications, and need for additional treatments.…”
Section: Discussionmentioning
confidence: 99%
“…First, elevated RDW level was correlated with elevated IL-6, circulating cytokines, and tumour necrosis factoralpha which affected aggressive tumour cell behavior (23). Reactive oxygen species and tissue hypoxia increased as RDW level increased, and these factors were associated with high risk of postoperative complications (24). Second, previous studies indicated that RDW level was associated with inflammation markers such as C-reactive protein and erythrocyte sedimentation rate, which demonstrated that RDW level may be an inflammatory marker (25,26).…”
Section: Nomogram For Os Predictionmentioning
confidence: 99%